Risk factors and the prevalence of anorexia nervosa among female students in Serbia - Lazarević, Jovana; Batinić, Borjanka; Vukosavljević-Gvozden, Tatjana (Vojnosanitetski pregled, 2017)
Background/Aim. The widespread symptoms of anorexia nervosa (AN) in young women require to draw professional attention to this problem in Serbia. In previous research on AN, insecure attachment styles, perfectionism and concerns about body shape were identified as notable risk factors. The aim of this study was to identify the prevalence of AN among female students and assess the importance of these factors in its development. Methods. The Eating Attitudes Test (EAT-40), the Experiences in Close Relationships Scale (ECR), the Frost Multidimensional Perfectionism Scale (FMPS) and the Body Shape Questionnaire (BSQ) were applied to a sample of 500 randomly selected female students of the University of Belgrade, the mean age of 22.44 years (min 18, max 35). In addition, Body Mass Index (BMI) was also calculated. Results. Although 38 (7.6%) female students displayed symptoms of AN (EAT > 30) and 13 (2.6%) had BMI indicating anorexia nervosa syndrome (BMI ≤ 17.50 kg/m2), only 1 (0.2%) student fulfilled both criteria. The majority of female students (60.4%) had some type of insecure attachment style. There is a significant influence of attachment styles on symptoms of AN: female students with insecure attachment styles have a significantly higher mean score on the EAT compared to those with secure attachment style (F = 7.873; p < 0.01). There was a positive correlation between scores on the EAT and FMPS (r = 0.217; p < 0.01), and scores on the EAT and BSQ (r = 0.388; p < 0.01). Conclusions. The obtained results show the prevalence of AN of 0.2% among female students and indicate the importance of insecure attachment styles, perfectionism and concern about body shape as risk factors. Activities for the prevention of AN in this subpopulation should include internet-based therapy and special counseling services with specific programs focusing on emotion-regulation skills through mindfulness, acceptance and commitment techniques, as well as specific cognitive-behavioral techniques.